Approach to the Description of Macro Lead Formation by Means of a Kinematics Simulation Model. Issue 4 (4th July 2022) - Haffner, Georg; Baumann, Matthias; Schmuker, Stefan; Bauer, Frank
Abstract: The often-recommended plunge grinding of lead-free sealing counterfaces for rotary shaft seals proposes a problem in production. The recommendations in references ( 1 ) and ( 2 ) tend to longer spark-out times, which is not cost-effective. Switching to more cost-effective alternative manufacturing methods can lead to a different unfavourable behavior of a sealing system ( 3, 4 ) . Thus, a more detailed look at the machining process called "plunge grinding" with its influence on the sealing counterface can help to improve the process parameters. Therefore, the plunge grinding process is considered kinematically in a simulation model. Kinematically simulated and modeled sealing counterfaces are then evaluated with statistical analysis software, where the resulting characteristics of the lead structures are compared with the input parameters of the process. Different parameter sets were also ground, analyzed, and evaluated to validate the results. With the good accordance between the kinematics simulation model the experimentally ground surfaces, this approach shows comprehensively the interrelationships between the manufacturing parameters and the resulting lead parameters.